2012
DOI: 10.1155/2012/396347
|View full text |Cite
|
Sign up to set email alerts
|

Does Death of a Family Member Moderate the Relationship between Religious Attendance and Depressive Symptoms? The HUNT Study, Norway

Abstract: Background. The death of a family member is a stressful life event and can result in an increased level of depressive symptoms. Previous American research has shown inverse relationships between religious involvement and depression. European investigations are few and findings inconsistent; different contexts may have an important influence on findings. We therefore investigated the relationship between attendance at church/prayer house and depressive symptoms, and whether this relationship was moderated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Older adults with a spouse have better physical and mental health and live longer (Manzoli, Villari, Pirone, & Boccia, 2007; Scafato et al, 2008; Schoenborn & Heyman, 2009; Tower, Kasl, & Darefsky, 2002). Others have linked being partnered to psychological well-being (Reneflot & Mamelund, 2012; Sørensen, Danbolt, Holmen, Koenig, & Lien, 2012), happiness and enjoyment in life (Kalfoss & Halvorsrud, 2009), and quality of life (Halvorsrud & Kalfoss, 2016). It may be that family forms such as being married or partnered provide purpose and meaning to life, mutual systems of support, and reduce loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with a spouse have better physical and mental health and live longer (Manzoli, Villari, Pirone, & Boccia, 2007; Scafato et al, 2008; Schoenborn & Heyman, 2009; Tower, Kasl, & Darefsky, 2002). Others have linked being partnered to psychological well-being (Reneflot & Mamelund, 2012; Sørensen, Danbolt, Holmen, Koenig, & Lien, 2012), happiness and enjoyment in life (Kalfoss & Halvorsrud, 2009), and quality of life (Halvorsrud & Kalfoss, 2016). It may be that family forms such as being married or partnered provide purpose and meaning to life, mutual systems of support, and reduce loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The former is also the picture in Norway regarding frequency distribution of RA [ 4 ], but women seem to have a kind of a durative approach to religious activity, maintaining the same level of religiousness independent of demanding events and/or illness. Norwegian men, on the other hand, tend to activate religiousness when demanding events and/or illness occur [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, any virtual religious gathering becomes the only viable means for people with physical or psychological difficulties. This suits well with men who are experiencing illness or stress as studies have shown that men tend to frequent church more often if they don't feel well (la Cour, 2008;Sørensen et al, 2012).…”
Section: Mental Health and Wellbeing -Letter To The Editor Dear Editormentioning
confidence: 76%